TNFAIP3 genetic polymorphisms reduce ankylosing spondylitis risk in Eastern Chinese Han population - Yang, Jiajia (Sci Rep, 2019)
This study was conducted to clarify the associations of tumor necrosis factor-α induced protein 3 (TNFAIP3) and TNFAIP3-interacting protein 1 (TNIP1) genetic polymorphisms with ankylosing spondylitis (AS) susceptibility. Five single nucleotide polymorphisms (SNPs) in TNFAIP3 gene and four in TNIP1 gene were genotyped in 667 AS patients and 667 matched healthy controls. Genotypes and haplotype analysis were conducted by using SPSS 23.0 and Haploview 4.2 software. The T allele and CT genotype in TNFAIP3 rs10499194 were significantly associated with a reduced AS risk (T allele vs. C allele, OR = 0.619, 95% CI = 0.430–0.889, P = 0.009; CT vs. CC, OR = 0.603, 95% CI = 0.416–0.875, P = 0.007). However, no association remained significant after Bonferroni correction. The rs13207033(A)- rs10499194(T) haplotype of TNFAIP3 conferred a protective effect on AS susceptibility. Stratification analyses suggested that rs10499194 polymorphism decreased the risk of AS in the male subgroup, subgroup aged ≥ 29, HLA-B27 positive subgroup as well as the subgroups of BASFI < 4 and BASDAI < 4 (all P < 0.05). Furthermore, the functional annotation suggested a potential function of rs10499194 mutation. Our results demonstrated that TNFAIP3 rs10499194 polymorphism may be associated with a reduced risk of AS.